1993
DOI: 10.1111/j.1365-2249.1993.tb03451.x
|View full text |Cite
|
Sign up to set email alerts
|

DistinctH-2complex control of mortality, and immune responses to tuberculosis infection in virgin and BCG-vaccinated mice

Abstract: SUMMARYWe have studied the impact of distinct haplotypes and of difTerent alleles at specific H-2 loci on: (i) the susceptibility to lethal form of experimental tubereulosis; (ii) the level of DTH to mycobaclerial antigens; (iii) the efficacy of vaccination wilh bacille Calmette-Gucrin (BCG); and (iv) the IgG production and Tcell proliferative response to H37Rv antigens. On lhe basis of median survival lime (MST) following primary inoculation wilh lethal dose of Myeobaeterium tutwrcidosis, susceptibility to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Similarly, other studies have demonstrated necrotic, encapsulated granulomas in mice possessing the sst1 genetic susceptibility locus (34), although encapsulated granulomas were associated with increasing bacterial loads during primary Mtb infection and only associated with low CFU following a course of isoniazid treatment. Similar to other susceptible mouse strains (35-39), the CBA/J mouse can form large coalescing nodular structures during Mtb infection however these are highly associated with end stages of disease, abundant CFU, and substantial lung involvement (not shown). This does however indicate a predisposition to develop fibrotic structures in CBA/J and other susceptible mouse strains that, as we show here, can lead to mature granulomas that are associated with protection in the absence of IL-10.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, other studies have demonstrated necrotic, encapsulated granulomas in mice possessing the sst1 genetic susceptibility locus (34), although encapsulated granulomas were associated with increasing bacterial loads during primary Mtb infection and only associated with low CFU following a course of isoniazid treatment. Similar to other susceptible mouse strains (35-39), the CBA/J mouse can form large coalescing nodular structures during Mtb infection however these are highly associated with end stages of disease, abundant CFU, and substantial lung involvement (not shown). This does however indicate a predisposition to develop fibrotic structures in CBA/J and other susceptible mouse strains that, as we show here, can lead to mature granulomas that are associated with protection in the absence of IL-10.…”
Section: Discussionmentioning
confidence: 77%
“…It has been demonstrated during the past 15 years that the whole haplotypes and alleles of certain genes within the major histocompatibility complex (MHC) influence susceptibility and immune responses to Mycobacterium tuberculosis in mice [1][2][3][4][5][6] and humans [7][8][9][10][11]. In two independent, genome-wide scans in two different mouse strain combinations, quantitative trait loci (QTL) involved in tuberculosis (TB) severity control were mapped within the H2 complex [12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, earlier studies have demonstrated that outcomes of vaccination 24, 3537 and the rate of relapse after chemotherapy 38, 39 are determined by genetic background of the mouse hosts. As no single human represents a genetically diverse population, neither does an individual mouse strain.…”
mentioning
confidence: 99%